Regional Variations of Medicare Physician Payments for Hand Surgery Procedures in the United States. (March 2019) - Veltre, David R.; Yakavonis, Mark; Curry, Emily J.; Cusano, Antonio; Parisien, Robert L.; Eichinger, Josef K.; Duncan, Scott F.M.; Stein, Andrew B.; Li, Xinning
Background: Medicare reimbursement is known to exhibit geographic variation for inpatient orthopedic procedures. This study determined whether US geographic variations also exist for commonly performed hand surgeries.Methods: Using the Medicare Provider Utilization and Payment Data (2012-2013) from Centers for Medicare & Medicaid Services, we analyzed regional physician charges/payments for common outpatient hand surgeries.Results: The most commonly performed procedures in the United States were open carpal tunnel release (n = 21 944), trigger finger release (n = 15 345), endoscopic carpal tunnel release (n = 7106), and basal joint arthroplasty/ligament reconstruction and tendon interposition (n = 2408). A range of average Medicare physician reimbursements existed based on geographic region for basal joint arthroplasty ($669-$571), endoscopic carpal tunnel release ($400-$317), open carpal tunnel release ($325-$261), and trigger finger release ($215-$167). The latter three exhibited statistically significant variation across geographic regions with regard to both charges and physician reimbursement. However, the overall percentage physician reimbursement (70%-79%) to charges was similar across all geographic regions.Conclusions: In conclusion, further research is warranted to determine why regional or geographic variations in physician payments exist in the United States for commonly performed hand surgeries.